2019
DOI: 10.9734/ijpss/2019/v28i330106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphorus Fertilizer Rates on Yield and Yield Components of Faba Bean (Vicia faba L.) Varieties in Lemu Bilbilo District of Arsi Zone, Southeastern Ethiopia

Abstract: Faba bean production is a common practice in Lemu Bilbilo areas. However, faba bean productivity is affected and limited by poor soil fertility and lack of alternative technologies such as application of optimum phosphorus fertilizer for different faba bean varieties. In view of this, a field experiment was conducted on farmer's field during the 2017 main cropping season at Lemu Bilbilo with the objectives to determine the response of faba bean varieties to different rates of P fertilizer and its influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…Significantly higher mean dry biomass yield (14,158 kg ha −1 ) and seed yield (6323 kg ha −1 ) were produced with the application of 40 kg P ha −1 that was at par with 20 kg P ha −1 and 30 kg P ha −1 at Lemu-Bilbilo. The results also showed that the grain yield of faba bean was significantly increased with P fertilizer application rates over the control whereas the application of 30 kg P ha −1 resulted in a higher number of effective tillers plant −1 (1.53), which was at par with all other P rates application except the unfertilized plots [29]. The highest grain yield of 3.2 t ha −1 was obtained from the application of 92 kg ha −1 P 2 0 5 at the Sekela district of West Gojam [30].…”
Section: Phosphorusmentioning
confidence: 80%
See 1 more Smart Citation
“…Significantly higher mean dry biomass yield (14,158 kg ha −1 ) and seed yield (6323 kg ha −1 ) were produced with the application of 40 kg P ha −1 that was at par with 20 kg P ha −1 and 30 kg P ha −1 at Lemu-Bilbilo. The results also showed that the grain yield of faba bean was significantly increased with P fertilizer application rates over the control whereas the application of 30 kg P ha −1 resulted in a higher number of effective tillers plant −1 (1.53), which was at par with all other P rates application except the unfertilized plots [29]. The highest grain yield of 3.2 t ha −1 was obtained from the application of 92 kg ha −1 P 2 0 5 at the Sekela district of West Gojam [30].…”
Section: Phosphorusmentioning
confidence: 80%
“…Under those conditions, the performance of individual plants becomes a limiting factor for maximum crop yield [44]. Source: [29].…”
Section: Plant Population and Patternsmentioning
confidence: 99%
“…The lack or low rates of essential elements like, Phosphorus in the soil is one of the factors negatively affect growth and yields of faba bean (Negasa et al, 2019). They also stated that, phosphate can readily be rendered unavailable to plant roots as it is the most immobile of the major plant nutrients.…”
Section: Effects Of Phosphorus On Faba Bean Productionmentioning
confidence: 99%
“…The major factors that are usually mentioned for the low yield of faba bean in Ethiopia include climatic, edaphic, biotic (diseases, pests and weeds) factors, and poor agronomic practices [9]. Majority of the farmers use low yielding of the local varieties which contribute for low production [10,11]. When comparing the yield of fababean in Ethiopia :it is below the world average due to several factors: among these lack of improved seed is a key [12].…”
Section: Background and Justifi Cationmentioning
confidence: 99%